C. C. W. Taylor (Editor), Oxford Studies in Ancient Philosophy. Volumen XIII (1994). Clarendon Press. Oxford 1994. 280 páginas. ISBN 0-19-823527-5 - Sacchi, Mario Enrique (1996)
Fil: Sacchi, Mario Enrique. Investigador Independiente; Argentina